”En disposition, form og orden” - Johan Heinsen (Akademisk Kvarter, 2012)
The article reads colonial texts about Jamestown, Virginia in the 17th century in the light of the assumption that they relate authority and sovereignty to geographical and spatial tropes. Sovereignty is synonymous with the ability to form a community. The formation of this can in this way be tied to a relationship between words, the law and topography.